The Relationship Between Resilience and Posttraumatic Growth Among the Primary Caregivers of Children With Developmental Disabilities: The Mediating Role of Positive Coping Style and Self-Efficacy - Wan Lu; Chen Xu; Xiankang Hu; Ju Liu; Qianhui Zhang; Li Peng; Min Li; Wenzao Li (Frontiers in Psychology, 2022)
This study was conducted to investigate the relationship between posttraumatic growth (PTG), resilience, positive coping style, and self-efficacy among the primary caregivers of children with developmental disorders in Chongqing, China. A total of 198 primary caregivers (parents and grandparents) aged from 22 to 66 years old (M = 35.55, SD = 9.16), including 155 females (78.3%) and 43 males (21.7%), were enrolled. The Posttraumatic Growth Inventory, Connor-Davidson Resilience Scale-10, Simplified Coping Style Questionnaire, and General Self-Efficacy Scale were used for data collection. The results found that PTG could be positively predicted by resilience. Positive coping style and self-efficacy mediated the relationship between resilience and PTG. The different levels of PTG were determined by the resident location, monthly income and education of the primary caregivers. The results suggest that it is critical to improve the mental health of the primary caregivers (parents and grandparents) of children with developmental disabilities. Our results also provide a scientific basis for future research.